Laboratory model study of newly deposited dredger fills using improved multiple-vacuum preloading technique - Jingjin Liu; Huayang Lei; Gang Zheng; Haizuo Zhou; Xuelian Zhang (Journal of Rock Mechanics and Geotechnical Engineering, 2017)
Problems continue to be encountered concerning the traditional vacuum preloading method in field during the treatment of newly deposited dredger fills. In this paper, an improved multiple-vacuum preloading method was developed to consolidate newly dredger fills that are hydraulically placed in seawater for land reclamation in Lingang Industrial Zone of Tianjin City, China. With this multiple-vacuum preloading method, the newly deposited dredger fills could be treated effectively by adopting a novel moisture separator and a rapid improvement technique without sand cushion. A series of model tests was conducted in the laboratory for comparing the results from the multiple-vacuum preloading method and the traditional one. Ten piezometers and settlement plates were installed to measure the variations in excess pore water pressures and moisture content, and vane shear strength was measured at different positions. The testing results indicate that water discharge–time curves obtained by the traditional vacuum preloading method can be divided into three phases: rapid growth phase, slow growth phase, and steady phase. According to the process of fluid flow concentrated along tiny ripples and building of larger channels inside soils during the whole vacuum loading process, the fluctuations of pore water pressure during each loading step are divided into three phases: steady phase, rapid dissipation phase, and slow dissipation phase. An optimal loading pattern which could have a best treatment effect was proposed for calculating the water discharge and pore water pressure of soil using the improved multiple-vacuum preloading method. For the newly deposited dredger fills at Lingang Industrial Zone of Tianjin City, the best loading step was 20 kPa and the loading of 40–50 kPa produced the highest drainage consolidation. The measured moisture content and vane shear strength were discussed in terms of the effect of reinforcement, both of which indicate that the multiple-vacuum preloading method has a better treatment effect not only in decreasing the moisture content and increasing the bearing capacity, but also in increasing the process uniformity at different depths of foundation.